2011
DOI: 10.1021/ja2040909
|View full text |Cite
|
Sign up to set email alerts
|

A More Reactive Trigonal-Bipyramidal High-Spin Oxoiron(IV) Complex with a cis-Labile Site

Abstract: The trigonal bipyramidal high-spin (S = 2) oxoiron(IV) complex [FeIV(O)(TMG2dien)(CH3CN)]2+ (7) was synthesized and spectroscopically characterized. Substitution of the CH3CN ligand by anions, demonstrated here for X = N3− and Cl−, yielded further S = 2 oxoiron(IV) complexes of general formulation [FeIV(O)(TMG2dien)(X)]+ (7-X). The reduced steric bulk of 7 relative to the published S = 2 complex [FeIV(O)(TMG3tren)]2+ (2) was reflected by enhanced rates of intermolecular substrate oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
110
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(116 citation statements)
references
References 38 publications
5
110
0
1
Order By: Relevance
“…[136] Moreover, it was demonstrated that S = 2 state models show only comparable (or even lower) reactivity towards OAT or HAA. [202,203,204,205] These observations emphasized the need for the correlation of reactivity with electronic structure as well as the geometric and steric properties of a complex. The study of Sastri et al [174] provided a comprehensive correlation between the electronic structure properties (reflected by the reduction potentials) and reactivity.…”
Section: Mononuclear Ferryl Active Sitementioning
confidence: 99%
“…[136] Moreover, it was demonstrated that S = 2 state models show only comparable (or even lower) reactivity towards OAT or HAA. [202,203,204,205] These observations emphasized the need for the correlation of reactivity with electronic structure as well as the geometric and steric properties of a complex. The study of Sastri et al [174] provided a comprehensive correlation between the electronic structure properties (reflected by the reduction potentials) and reactivity.…”
Section: Mononuclear Ferryl Active Sitementioning
confidence: 99%
“…A series of intermediate-spin S ¼ 1 Fe IV ═O model complexes, supported by amine, pyridine, and deprotonated amido ligands, has become available for structural, reactivity, and spectroscopic investigations (7)(8)(9)(10)(11)(12)(13). Recently, high-spin S ¼ 2 Fe IV ═O complexes have also become available, with two being structurally defined (14)(15)(16)(17)(18)(19)(20), but notably their reactivity does not surpass that of the most reactive S ¼ 1 complexes (15,18,21).…”
Section: S ¼ 2 Fementioning
confidence: 99%
“…13 While most of the Fe IV ═O model complexes have low-spin ( S = 1) ground states, 14 some models have the S = 2 spin state that is present in the enzymatic intermediates. 15 A combined spectroscopic and computational study of one of the S = 2 model complexes, (TMG 3 tren)Fe IV ═O, 15a elucidated three reactive channels available for HAA: two are active when the C–H bond is oriented perpendicular to the Fe–oxo bond ( π channels leading to S Fe = 5/2 or S Fe = 3/2 Fe III –OH intermediates) and one that is active for C–H bonds oriented along the Fe–oxo bond ( σ channel providing an S Fe III = 5/2 intermediate). 16 This is strikingly different from the S = 1 Fe IV ═O complexes, which have only one available channel, π ( S Fe III = 3/2).…”
Section: Introductionmentioning
confidence: 99%